2018 International Conference on Radar (RADAR) 2018
DOI: 10.1109/radar.2018.8557258
|View full text |Cite
|
Sign up to set email alerts
|

Radar Cross Section of Modified Target Using Gaussian Beam Methods: Experimental Validation

Abstract: The aim of this paper is to study the Radar Cross Section (RCS) of modified radar targets (plate with notch) using Gaussian Beam techniques. The Gaussian methods used in this work are Gaussian Beam Summation (GBS) and Gaussian Beam Launching (GBL). We establish the theoretical formulation of the GBS and GBL techniques and analyze the influence of the main Gaussian beam parameters on the variation of the scattered field. Then, we present the simulations of RCS. The numerical results are compared with PO, MoM me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…On the other hand, when r = 0, the curves of GBS method do not have singularities. This result confirms that by using the GBS method can solve some limitations of the ray asymptotic models (singularities) [20, 23].…”
Section: Introduction and Formulation Of Gbs And Gblsupporting
confidence: 81%
See 3 more Smart Citations
“…On the other hand, when r = 0, the curves of GBS method do not have singularities. This result confirms that by using the GBS method can solve some limitations of the ray asymptotic models (singularities) [20, 23].…”
Section: Introduction and Formulation Of Gbs And Gblsupporting
confidence: 81%
“…In the previous works [20–23], both GBS and GBL techniques are applied for the simulation of canonical and modified target RCS. It was found that the purposed composite GBS/GBL + PTD provide an accurate representation of the scattered field.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations